Lecturer Performance: Implementation of the 3 Milestone Improvement Model in Improving Lecturer Performance - Yohamintin, Yohamintin; Suharjuddin, Suharjuddin; Gumala, Yosi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research is motivated by the need in education, especially Bhayangkara University, Greater Jakarta, for quality human resources to improve the quality of education. The performance of PGSD lecturers still needs to be optimal in terms of improvement, even though the demand for superior human resources is necessary for the university's goal of becoming exceptional. Attention to lecturer performance is the aim of this research, where the application of 3 Miles Stone Improvement strategic management is a solution to improve the performance of PGSD lecturers, especially in sustainable professional competence. This research is qualitative research with a case study method. Data was collected using interview instruments, observation guidelines, and document review guidelines. This research consists of 2 stages: the implementation of the 3-mile stone improvement model to improve lecturer performance, and the second stage is follow-up in the form of evaluation of the implementation and modification of the model or program therein. The research results reveal that implementing the model increases lecturer performance, seen from 1-semester running, and a 50% increase in performance, seen from the achievement of the lecturer certification process and promotion of lecturer academic positions.